EXTENT OF HEPATOTOXICITY OF ANTI-TUBERCULOSIS DRUGS USED IN PAKISTAN: A CROSS-SECTIONAL STUDY - Shahid, Sara; Ahmed, Fahad; Mustafa, Abid; Sana, Anosh; Khan, Rabeel; Shahzad, Seerat; Zulfiqar, Ayesha; Farooq, Hamza; Abbas, Sameen; Razzaq, Tabinda; Amjad, Umair; Ali, Wasiq; et al. (Universal Journal of Pharmaceutical Research, 2023)
Introduction: Tuberculosis is an infectious disease with high rates of infection and mortality throughout the world, but its spread is greater in developing countries, and its control is difficult. It is known that the most common side reaction of drug treatment for tuberculosis is hepatotoxicity resulting from the drugs, which negatively affects adherence to treatment as a result of patients not continuing to use it. Objective:This study aimed to determine the extent of hepatotoxicity as a result of drug treatment for tuberculosis. Methods: The study is a cross-sectional study conducted on TB patients undergoing TB treatment in a general hospital in Islamabad, Pakistan. A data collection form was used to obtain demographic and treatment data. The hepatotoxicity of TB drug therapy was evaluated by performing liver function tests (LFTs).Study duration was of 4 months. Results: The study showed that out of 100 tuberculosis patients, 55 patients were hepatotoxic. Hepatotoxic population includes 26% males and 29% females including almost 10% children either male or female. The maximun hepatotoxicity was observed in the patients undergoing combination therapy. Around 3-5 % patients showed that the Serum-GlutamicPyruvic-Transaminase (SGPT) values more than 2 times of their normal values. While other 50% showed hepatotoxicity 1-2 times of their normal values. Most of the patients found were in the age group ranging from 35-60 years. The main drugs used in tuberculosis treatment were: Isoniazid, Rifampicin, Pyrazinamide, Ethambutal. Conclusion:The rate of hepatotoxicity in TB patients on anti-TB treatment was high. The current study concluded that the more we move towards a greater number of drugs in combination, the greater the extent and chance of hepatotoxicity. The combination of three anti-tuberculosis drugs (isoniazid, rifampicin, and pyrazinamide) resulted in maximum hepatotoxicity. Peer Review History: Received: 9 August 2023; Revised: 10 September; Accepted: 29 October; Available online: 15 November 2023 Academic Editor: Dr. Marwa A. A. Fayed , University of Sadat City, Egypt, maafayed@gmail.com Reviewers: Dr. Owanaro Peter, Nigeria, Department of Clinical Pharmacy and Pharmacy Practice, Faculty of Pharmacy, Niger Delta University, Wilberforce Island, Bayelsa State, Nigeria. owonaropeter@gmail.com Prof. Hassan A.H. Al-Shamahy, Sana’a University, Yemen, shmahe@yemen.net.ye Dr. Sheikh Abdul Khaliq, Department of Pharmacy Practice, Faculty of Pharmacy, Hamdard University, Karachi, Pakistan, drwadhsheikh1974@gmail.com